International Human Rights Institutions, Tribunals, and Courts - Oberleitner, Gerd (Springer Singapore, 2018)
Chapter 1: Human rights institutions: what legitimacy? what authority? -- Part 1: United Nations human rights institutions -- Chapter 3: The UN Human Rights Council: achievements 2006-2016 and challenges ahead -- Chapter 4: The UN High Commissioner for Human Rights and field operations -- Chapter 5: UN Human Rights Treaty Bodies: impact and future -- Chapter 6: The UN Human Rights Committee -- Chapter 7: The UN Committee of Economic, Social and Cultural Rights -- Chapter 8: Gender in the UN: CEDAW and the Commission on the Status of Women -- Chapter 9: The UN Security Council and human rights -- Chapter 10: Why a World Court of Human Rights? -- Part 2: Human rights violations as crimes - international courts and tribunals -- Chapter 11: The Legacy of Nuremberg and Tokyo -- Chapter 12: Prosecuting human rights violations: what legacy of the ad hoc criminal tribunals for the former Yugoslavia and Rwanda? -- Chapter 13: What future for ad hoc tribunals? -- Chapter 14: The International Criminal Court between human Rights and realpolitik -- Chapter 15: Towards effective enforcement of international humanitarian law -- Chapter 16: Transitional Justice: the legacy and future of Truth and Reconciliation Commissions -- Part 3: Regional human rights systems -- Chapter 17: The European Court of Human Rights: achievements and prospects -- Chapter 18: The Inter-American Commission and Court of Human Rights -- Chapter 19: The African Commission on Human and Peoples’ Rights and the African Court of Justice and Human and Peoples' Rights -- Chapter 20: The Arab Human Rights Commission -- Chapter 21: The ASEAN Human Rights Commission -- Chapter 22 : An Agenda for Strengthening Human Rights Institutions.
Keywords: Aufsatzsammlung; Vereinte Nationen; Internationale Gerichtsbarkeit; Internationales Recht; Menschenrecht; Menschenrechtsorganisation